Association between Physical Fitness and Low Back Pain: The Pepe Cross-Sectional Study - Aina M. Galmés-Panadés; Josep Vidal-Conti (MDPI AG, 2022)
Background: Recent studies have shown that the lifetime prevalence of low back pain (LBP) in schoolchildren aged 10-12 years is 73.6%, and that it appears to have an impact on people's quality of life. A wide range of risk factors associated with LBP have been studied. However, inconsistent results have been reported. In recent decades, the physical fitness level of children and adolescents has worsened, and the current data on the relationship between muscular fitness and musculoskeletal pain are ambiguous. The purpose of the present study was to analyze the relationship between physical fitness and the occurrence and intensity of LBP. Methods: This cross-sectional study assessed 849 students, aged 10-12 years, from 10 primary schools (fifth and sixth grades) from Majorca (Spain). It was based on two different structured and self-administered questionnaires and a fitness test battery validated for child populations. Results: The results showed that higher levels of VO2Max correspond to less LBP intensity. Additionally, LBP was less prevalent among participants who self-reported more physical activity, and higher VO2Max and higher levels of flexibility were associated with the absence of LBP in bed. Conclusion: These results are of particular importance, as cardiorespiratory fitness is the parameter most closely related to health, and it seems to also be related to LBP-prevention.